COFFEE FARMERS PERCEPTION OF CLIMATE CHANGE AND SOCIOECONOMICS FACTORS AFFECTING THE ADOPTION OF CLIMATE SMART AGRICULTURE (CSA) IN LAMPUNG PROVINCE - Fardinatri, Intan Diani; Hasanuddin, Tubagus; Saputro, Sumaryo Gito (Universitas Pahlawan Tuanku Tambusai, 2024)
This research focused on the effect of perception and socioeconomic factors in adoption of Climate Smart Agriculture (CSA) and coffee productivity. It was conducted in one Community Forest in Indonesia. Results indicate that the farmers perception and land size farming significantly related to CSA adoption. The farmers’ perception to CSA, their household income, and land size are significantly correlated with the coffee productivity and number of days invested on coffee farms for CSA practices such as in fertilizing, pruning, and pests and diseases control. Farmers with positive perception have allocated 44.98% more time and therefore gain more productivity of 38.99%.